On Initial Boundary Value Problems with Equivalued Surface for Nonlinear Parabolic Equations. (16th June 2009) - Li, Fengquan
Abstract : We will use the concept of renormalized solution to initial boundary value problems with equivalued surface for nonlinear parabolic equations, discuss the existence and uniqueness of renormalized solution, and give the relation between renormalized solutions and weak solutions.